Stretch treatment: research focused on aesthetic biomedicine - Oliveira, Cecília Carvalho de; Chaves, Raquel (Revista Coleta Científica, 2019)
Increasingly, the aesthetic procedure has been sought with objectives ranging from personal satisfaction to pathological treatments. Every day new protocols are created, new aesthetic devices and instruments, new cosmetic formulations, all with one purpose: to keep the skin young and free from imperfections. One of the treatments that has been shown to be very efficient in this regard is micropuncture. A technique that consists of damaging the most superficial layers of the skin in order to cause controlled inflammation, and promote the activation of collagen cells. The increase in these cells activates the production of collagen and elastin, substances responsible for the firmness and elasticity of the skin. The micropuncture technique in the treatment of stretch marks andinvestigate the effects.It should be noted that the success of the technique goes beyond epithelial uniformity and, consequently, good tissue aesthetics, with benefits for the patient’s self-esteem and personal satisfaction of the professional, who has in his hands the possibility of observing the evident improvement of the patient’s skin, as long as hold the knowledge and properly execute the micropuncture. that micropuncture is an effective technique in the treatment of stretch marks, with the reduction in size, in millimeters, provides an improvement in the framework of this dysfunction. Some assets help in the process of formation of collagen and elastin, promoting the filling of the skin, changing its appearance.